2013
DOI: 10.1186/2110-5820-3-19
|View full text |Cite
|
Sign up to set email alerts
|

How caregivers view patient comfort and what they do to improve it: a French survey

Abstract: BackgroundIntensive care unit (ICU) patients are exposed to many sources of discomfort. Most of these are related to the patient’s condition, but ICU design or how care is organized also can contribute. The present survey was designed to describe the opinions of ICU caregivers on sources of patient discomfort and to determine how they were dealt with in practice. The architectural and organizational characteristics of ICUs also were analyzed in relation to patient comfort.MethodsAn online, closed-ended questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
1
18
1
1
Order By: Relevance
“…Natural light is considered essential for ICUs [27]. One study reported that nurses thought that only 66.0% of the ICUs had natural light, which can affect the resting status of patients [28]. Eye masks were useful to improve the sleeping patterns of the ICU patients [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural light is considered essential for ICUs [27]. One study reported that nurses thought that only 66.0% of the ICUs had natural light, which can affect the resting status of patients [28]. Eye masks were useful to improve the sleeping patterns of the ICU patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…Patients stated that they felt environmental distress while in the ICU [13]. Some ICUs do not have natural light [28]. Additionally, the use of aromatherapy results in improvements in the mood and anxiety levels of ICU patients [29].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Thirst is poorly recognized in intensive care unit (ICU) practice. [4, 5] Yet, research has identified it as one of the most pervasive, intense, and under-treated symptoms in ICU patients. [6, 7] Over 70% of ICU cancer patients reported unsatisfied thirst at the highest levels of intensity, [8] and almost all chronically, critically ill patients in a hospital-based Respiratory Care Unit reported moderate or severe thirst.…”
Section: Introductionmentioning
confidence: 99%
“…Another study performed by Lombardo et al. () demonstrated that an insufficient number of ICUs are designed to preserve patient privacy and create a restful atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that a poor design in emergency departments does not allow privacy for dying patients or grieving family members (Attia et al, 2013). Another study performed by Lombardo et al (2013) demonstrated that an insufficient number of ICUs are designed to preserve patient privacy and create a restful atmosphere.…”
Section: Discussionmentioning
confidence: 99%